The views of key stakeholders around mandatory influenza vaccination of hospital and aged care staff: Examining the current climate in Australia. Issue 5 (29th January 2019) - Moran, Alexis; Agaliotis, Maria; Seale, Holly
Abstract: Background: Healthcare worker (HCW) vaccination against seasonal influenza is considered a key preventative measure within hospitals and aged-care facilities (ACFs) to reduce the risk of transmission and related disease. Despite this, many facilities experience persistently low vaccination coverage rates and mandatory vaccination has been explored as a potential strategy to improve coverage. This study explored the current climate around staff vaccination in Australia from the perspective of opinion leaders and key stakeholders. Methods: Qualitative semi-structured interviews were conducted between April and July 2018 with 22 individuals involved in vaccination policy and program development and implementation from a range of organisations including state health departments, hospitals and ACFs across Australia. In addition, interviews were undertaken with individuals from aged care and nursing peak bodies/colleges. Interviews were transcribed, and thematic analysis was undertaken using NVivo 12 software. Results: Major themes emerging from the interviews included a sense that attitudes around staff vaccination are changing; the persistence of administrative and resource barriers; the importance of positive workplace culture towards influenza vaccination; and the need for individualised and personal communication strategies. Perspectives were diverse on the necessity of introducing stronger policies, with participants divided in their support mandatory influenza vaccinations. Some advocated that key performance indicators should be used as an alternative to vaccine mandates. Conclusions: This study provides policy makers with useful insights into the current Australian context around occupational vaccination policies, to inform acceptable and effective strategies to improve influenza vaccination uptake among Australian hospital and aged care staff.